Microstructure and dynamic mechanical behavior of wire-arc additive manufactured high-strength steel - Jing-Jing Cheng; Cheng Xu; Tian-Yang Zhang; Shen He; Ke-Hong Wang (Journal of Materials Research and Technology, 2023)
The working environment of high-strength steel components produced by wire-arc additive manufacturing (WAAM) often faced challenges of explosion and impact, but the microstructure evolution and dynamic mechanical behavior of WAAM produced high-strength steel were still unclear. In this study, low alloy high-strength steel （HSS） components were produced by WAAM. Split Hopkinson Pressure Bar (SHPB) tests at different strain rates were carried out on WAAM-HSS, and the specimens before and after dynamic compression were characterized by techniques such as SEM, EDS, XRD, EBSD, etc. The results showed that： The as-built WAAM-HSS plate mainly consists of five typical structures: lath martensite (ML), acicular ferrite (AF), polygonal ferrite (PF), martensite-austenite (M-A), and precipitated phase δ. The central area of the precipitated phase is Si and Mn, and the C element is mainly distributed in the surrounding area of the precipitated phase. Under dynamic compression, the as-built WAAM-HSS exhibited obvious yield phenomenon, and the yield stress increased with the increase of strain rate. The yield-strengthening mechanism is mainly contributed by grain refinement strengthening mechanism and dislocation density strengthening mechanism. Under dynamic compression, the martensite transformation occurred in the WAAM-HSS. The deformation mechanism is dislocation slip and twinning, which compete with each other. Dislocation slip deformation is dominant at low strain rate and twinning deformation is more dominant at high strain rate.